1987
DOI: 10.1002/rcm.1290010111
|View full text |Cite
|
Sign up to set email alerts
|

Improved detection of ‘suppressed’ peptides in enzymic digests analyzed by fab mass spectrometry

Abstract: positive charge for each part of the molecules on ionization. The data are presented with the NH2 groups being treated as single units. This allows for the fact that removal of electrons from the nitrogen is compensated for by increased polarization of the N-H bonds. For urea the oxygen gains only 0.17+ whereas the sulphur of thiourea gains 0.71+. By contrast each amino group in urea gains 0.48+ whereas each amino group in thiourea gains only 0.12+. This is in broad agreement with our earlier proposal that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…During the analysis of peptide mixtures by positive ion FAB mass spectrometry, hydrophobic peptides have been shown to form more abundant protonated molecules relative to those from hydrophilic peptides in the mixture [9,10]. Caprioli and co-workers [9, 101 reported that continuous-flow FAB mass spectrometry reduced the ion suppression effects observed for mixtures of peptides during standard FAB mass spectrometry.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the analysis of peptide mixtures by positive ion FAB mass spectrometry, hydrophobic peptides have been shown to form more abundant protonated molecules relative to those from hydrophilic peptides in the mixture [9,10]. Caprioli and co-workers [9, 101 reported that continuous-flow FAB mass spectrometry reduced the ion suppression effects observed for mixtures of peptides during standard FAB mass spectrometry.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, FAB mass spectrometry has been coupled with high-performance liquid chromatography (HPLC) by Ito and co-workers [5][6][7] in a system called frit-FAB liquid chromatography mass spectrometry (frit-FAB LC/MS). A similar technique, continuous-flow FAB mass spectrometry, was developed by Caprioli and co-workers first for flow injection analysis (8)(9)(10) and later for LC/MS [11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chromatographic separation also minimizes suppression e †ects in biological extracts. 21 The use of B/E-linked mass spectrometric modes greatly reduced the chemical background originating from the extract and the FAB glycerol matrix. Quantitative analysis, performed by SRM with diagnostic transitions shown in Table 3 (bold entries), resulted in a sensitivity in the femtomole range ( Table 3).…”
Section: Advantages Of the New Cytokinin Derivatives For Lc/frit-fab-mentioning
confidence: 99%
“…The combination of these microcolumns with "soft" ionization techniques such as FAB permits not only the sensitive detection (typically <10 ng) of the various protonated molecular ions, but also exploitation of the inherent advantages of microcolumns, namely, high plate numbers (>50,000 theoretical plates per meter), high mass sensitivity «10 pmol per injection), and lower optimum flow rates [10]. Numerous applications using such interfaces have been reported for the analysis of peptide mixtures [11,12], permethylated oligosaccharides [13], and enzymatic digests of proteins [14][15][16][17][18][19].…”
mentioning
confidence: 99%